Genome-wide alteration in DNA hydroxymethylation in the sperm from bisphenol A-exposed men - Zheng, Huajun (PLoS One, 2017)
Environmental BPA exposure has been shown to impact human sperm concentration and motility, as well as rodent spermatogenesis. However, it is unclear whether BPA exposure is associated with alteration in DNA hydroxymethylation, a marker for epigenetic modification, in human sperm. A genome-wide DNA hydroxymethylation study was performed using sperm samples of men who were occupationally exposed to BPA. Compared with controls who had no occupational BPA exposure, the total levels of 5-hydroxymethylcytosine (5hmc) increased significantly (19.37% increase) in BPA-exposed men, with 72.69% of genome regions harboring 5hmc. A total of 9,610 differential 5hmc regions (DhMRs) were revealed in BPA-exposed men relative to controls, which were mainly located in intergenic and intron regions. These DhMRs were composed of 8,670 hyper-hMRs and 940 hypo-hMRs, affecting 2,008 genes and the repetitive elements. The hyper-hMRs affected genes were enriched in pathways associated with nervous system, development, cardiovascular diseases and signal transduction. Additionally, enrichment of 5hmc was observed in the promoters of eight maternally expressed imprinted genes in BPA-exposed sperm. Some of the BPA-affected genes, for example, MLH1, CHD2, SPATA12 and SPATA20 might participate in the response to DNA damage in germ cells caused by BPA. Our analysis showed that enrichment of 5hmc both in promoters and gene bodies is higher in the genes whose expression has been detected in human sperm than those whose expression is absent. Importantly, we observed that BPA exposure affected the 5hmc level in 11.4% of these genes expressed in sperm, and in 6.85% of the sperm genome. Finally, we also observed that BPA exposure tends to change the 5hmc enrichment in the genes which was previously reported to be distributed with the trimethylated Histone 3 (H3K27me3, H3K4me2 or H3K4me3) in sperm. Thus, these results suggest that BPA exposure likely interferes with gene expression via affecting DNA hydroxymethylation in a way partially dependent on trimethylation of H3 in human spermatogenesis. Our current study reveals a new mechanism by which BPA exposure reduces human sperm quality.